Pengaruh prosentase larutan NaOH pada proses alkalisasi serat kulit pohon waru (hibiscus tiliaceus) sebagai reinforcement komposit terhadap kekuatan tarik serat tunggal - Arief Rizki Fadhillah; Dadang Hermawan; Arie Restu Wardhani (TURBO [Tulisan Riset Berbasis Online], 2019)
The utilization of natural fiber, nowadays, has employed as reinforcement of composite materials. Natural fiber can benefit the composite material because of the characters of fibre which is more environmental friendly, economics, lighter and stronger. There are many natural fibers that can be used as reinforcement of composite materials such as the bark fibers of Hibiscus Tiliaceus. Hibiscus Tiliaceus is one species of Hibiscus Tiliaceus that can be found in the mountains in Indonesia. This study aims to determine the tensile strength of a single fiber in Hibiscus Tiliaceus fiber with the additional various percentage of NaOH in the alkalization treatment. The alkalization treatment analyzes the alkali process of NaOH substance by 3%, 6%, 9%, 12%, and without treatment within the bark of Hibiscus Tiliaceus tree. The treatment was undertaken by soaking the NaOH substance in a duration of 120 minutes. After the NaOH solution was immersed, the bark fiber of Hibiscus Tiliaceus was washed with aquades until the solution reaches a pH of 7. The results of this study show the percentage of NaOH solution in the alkaline immersion process affects the tensile strength of a single fiber on Hibiscus Tiliaceus and the process of NaOH solution which has a release of 6% lignin, cellulose, and semilulose content. In addition, the NaOH treatment with a percentage of 6% can be the standard of the process of alkalizing the bark fiber of Hibiscus Tiliaceus which can be used for composite reinforcement. Therefore, 6% of NaOH can affect the bond between the Hibiscus Tiliaceus fibers as reinforcement and synthetic resins as a matrix which can increase the strength of the composite.